The Clinical Profile of a Young Visually Handicapped Population - Gresset, J; Simonet, P (Canadian Journal of Optometry, 2021)
This paper presents the results of a study done at the low vision clinic at the lnstitut Nazareth et Louis-Braille in Longueuil, Quebec. The Institute offers rehabilitation services and visual aids to eligible visually impaired persons in western Quebec and serves both a partially sighted and functionally blind population, as defined by Genenskyl. A low vision examination is part of the Institute's admission procedure. Information derived from clinical files offers data on a complete population of visually impaired people, since it includes all levels of visual impairment.